The stability of covalent dative bond significantly increases with increasing solvent polarity - Lo, Rabindranath; Manna, Debashree; Lamanec, Maximilián; Dračínský, Martin; Bouř, Petr; Wu, Tao; Bastien, Guillaume; Kaleta, Jiří; Miriyala, Vijay Madhav; Špirko, Vladimír; Mašínová, Anna; Nachtigallová, Dana; et al. (Nature communications, 2022)
It is generally expected that a solvent has only marginal effect on the stability of a covalent bond. In this work, we present a combined computational and experimental study showing a surprising stabilization of the covalent/dative bond in Me3NBH3 complex with increasing solvent polarity. The results show that for a given complex, its stability correlates with the strength of the bond. Notably, the trends in calculated changes of binding (free) energies, observed with increasing solvent polarity, match the differences in the solvation energies (ΔEsolv) of the complex and isolated fragments. Furthermore, the studies performed on the set of the dative complexes, with different atoms involved in the bond, show a linear correlation between the changes of binding free energies and ΔEsolv. The observed data indicate that the ionic part of the combined ionic-covalent character of the bond is responsible for the stabilizing effects of solvents.
Keywords: rozpouštědla; termodynamika; ionty; Ions; Solvents; Thermodynamics